Human Osteoblast Migration in DC Electrical Fields Depends on Store Operated Ca2+-Release and Is Correlated to Upregulation of Stretch-Activated TRPM7 Channels - Rohde, Marco; Ziebart, Josefin; Kirschstein, Timo; Sellmann, Tina; Porath, Katrin; Kühl, Friederike; Delenda, Bachir; Bahls, Christian; van Rienen, Ursula; Bader, Rainer; Köhling, Rüdiger (Frontiers in Bioengineering and Biotechnology, 2019)
Fracture healing and bone regeneration, particularly in the elderly, remains a challenge. There is an ongoing search for methods to activate osteoblasts, and the application of electrical fields is an attractive approach in this context. Although it is known that such electromagnetic fields lead to osteoblast migration and foster mesenchymal osteogenic differentiation, so far the mechanisms of osteoblast activation remain unclear. Possible mechanisms could rely on changes in Ca2+-influx via ion channels, as these are known to modulate osteoblast activity, e.g., via voltage-sensitive, stretch-sensitive, transient-receptor-potential (TRP) channels, or store-operated release. In the present in vitro study, we explored whether electrical fields are able to modulate the expression of voltage-sensitive calcium channels as well as TRP channels in primary human osteoblast cell lines. We show migration speed is significantly increased in stimulated osteoblasts (6.4 ± 2.1 μm/h stimulated, 3.6 ± 1.1 μm/h control), and directed toward the anode. However, within a range of 154–445 V/m, field strength did not correlate with migration velocity. Neither was there a correlation between electric field and voltage-gated calcium channel (Cav3.2 and Cav1.4) expression. However, the expression of TRPM7 significantly correlated positively to electric field strength. TRPM7 channel blockade using NS8593, in turn, did not significantly alter migration speed, nor did blockade of Cav3.2 and Cav1.4 channels using Ni+ or verapamil, respectively, while a general Ca2+-influx block using Mg2+ accelerated migration. Stimulating store-operated Ca2+-release significantly reduced migration speed, while blocking IP3 had only a minor effect (at low and high concentrations of 2-APB, respectively). We conclude that (i) store operated channels negatively modulate migration speed and that (ii) the upregulation of TRPM7 might constitute a compensatory mechanism-which might explain how increasing expression levels at increasing field strengths result in constant migration speeds.